PENGARUH STRUKTUR MODAL DAN RISIKO OPERASIONAL TERHADAP PROFITABILITAS PERBANKAN (Studi Pada Perusahaan Perbankan yang Terdaftar Di BEI Tahun 2015-2019) - Elsa Hastuti Sudiman; Gusganda Suria Manda (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
This study aims to determine and examine the effect of capital structure and operational risk on the level of bank profitability (empirical study on banking on the IDX 2015-2019). The type of data used is secondary data obtained from www.idx.co.id. With a population of 44 companies and sampling using purposive sampling technique. The results of this study indicate that partially capital structure has no significant effect on profitability and operational risk has a significant effect on profitability. Meanwhile, the results of the research simultaneously state that the capital structure and operational risk jointly influence profitability.